Root Coverage Predictability in the Treatment of Gingival Recessions on Mandibular Anterior Teeth. (July 2022) - Agusto, M.; Salman, A.; Parker, D.; Choi, D.; Schincaglia, G.P.
Introduction: Mandibular anterior teeth are most frequently affected by gingival recession. However, data regarding mucogingival treatment aimed at root coverage in this specific location are limited. Objective: The purpose of this study was to systematically review the scientific literature and to use the meta-analytic approach to address the following focused question: "What is the effectiveness of different surgical approaches on clinical and patient-related outcomes in the treatment of buccal gingival recessions on mandibular anterior teeth?" Methods: Studies were located by searching 3 electronic databases (Medline, Scopus, and Cochrane databases) and cross-referencing. Randomized and nonrandomized studies including at least 1 arm involving the use of pedicle flaps and/or free soft tissue grafts in the treatment of gingival recessions (recession type [RT] 1 and RT2) located on the buccal aspects of mandibular centrals, laterals and canines, were included in the analysis. Primary outcome was mean root coverage (mRC), expressed in percentage, based on a 3- to 12-mo follow-up observation. A Bayesian single-arm network meta-analysis was performed to identify a treatment hierarchy of the different surgical techniques. Results: Sixteen studies, with a total of 23 arms, were included in the quantitative analysis. The greatest mRC is associated with laterally positioned flap (LPF) + connective tissue graft (CTG) (91.2%) and tunnel (TUN) + CTG (89.4%), whereas LPF alone, coronally advanced flap (CAF) + CTG, and free gingival graft (FGG) showed lower mRC (79.1%, 78.9%, and 68.5% respectively). TUN + CTG provides significantly greater mRC compared to CAF+CTG. No difference among the procedures could be observed in terms of keratinized tissue width gain. Conclusions: Treatment hierarchy generated by an arm-based network meta-analysis model suggested that tunnel and laterally positioned flap, both in combination with connective tissue graft, may provide the greatest mean root coverage in the treatment of mandibular anterior recessions. Knowledge Transfer Statement: The results of the present systematic review can be used by clinicians when deciding which approach to adopt when treating buccal gingival recessions on mandibular anterior teeth. In particular, procedures based on a laterally positioned flap or a tunneling technique, both in combination with connective tissue graft, seem to be the most predictable therapeutic decision.